2018
DOI: 10.18632/oncotarget.26143
|View full text |Cite
|
Sign up to set email alerts
|

In tumor cells, thyroid hormone analogues non-immunologically regulate PD-L1 and PD-1 accumulation that is anti-apoptotic

Abstract: The PD-1/PD-L1 immune checkpoint involving tumor cells and host immune defense lymphocytes is a well-studied therapeutic target in oncology. That PD-1 and PD-L1 may have additional functions within tumor cells that are independent of the checkpoint is indicated by actions of a thyroid hormone analogue, L-thyroxine (T4), on these checkpoint components. Acting at a cell surface receptor on plasma membrane integrin αvβ3, T4 stimulates intracellular accumulation of PD-L1 in cancer cells. In these thyroid hormone-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…At present, cutting-edge immunotherapies promise PTC patients another alternative treatment method. In vitro and/or in vivo experiments proposed that immune checkpoint inhibitors could boost the effective elimination of thyroid tumor cells [22,23]. Besides, Bai Y et al found that the expression of BRAF V600E is positively correlated with PD-L1/PD-1 in PTC samples, which indicated that immune checkpoint therapy might be effective for PTC patients with the BRAF V600E mutation [24].…”
Section: Introductionmentioning
confidence: 99%
“…At present, cutting-edge immunotherapies promise PTC patients another alternative treatment method. In vitro and/or in vivo experiments proposed that immune checkpoint inhibitors could boost the effective elimination of thyroid tumor cells [22,23]. Besides, Bai Y et al found that the expression of BRAF V600E is positively correlated with PD-L1/PD-1 in PTC samples, which indicated that immune checkpoint therapy might be effective for PTC patients with the BRAF V600E mutation [24].…”
Section: Introductionmentioning
confidence: 99%
“…At present, cutting-edge immunotherapies promise PTC patients another alternative treatment method. In vitro and/or in vivo experiments proposed that immune checkpoint inhibitors could boost the effective elimination of thyroid tumor cells [22,23]. Besides, Bai Y et al found that the expression of BRAF V600E is positively correlated with PD-L1/PD-1 in PTC samples, which indicated that immune checkpoint therapy might be effective for PTC patients with the BRAF V600E mutation [24].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the positive expression of PD-L1 seems to indicate that the type of thyroid cancer originates from thyroid follicular epithelial cells. Lin et al [ 30 ] reported that acting at a cell surface receptor on plasma membrane integrin αvβ3, thyroxine produced by thyroid follicular epithelial cells stimulates intracellular accumulation of PD-L1 in cancer cells and induces downstream signaling pathways that promote tumor cell proliferation, such as mitogen-activated protein kinase (MAPK)/extracellular signal regulated kinase and phosphatidylinositol-3-kinase/protein kinase B pathways, which can promote PD-L1 overexpression. Our results on OS differ from those of Girolami study [ 16 ] ; unfortunately, our study on OS only included 3 articles, which may have affected the final result.…”
Section: Discussionmentioning
confidence: 99%